Hubungan Jurnalistik Bentuk dan Makna: Analisis Tematik Konten Berita Al-Jazeera dan Mu’jam Mustalahat al-I’lamiyah - Darsita Suparno; bila, Salsabila Ramli; MauidlotunNisa’; Kaula Fahmi; UlilAbshar; Zamzam Nurhuda (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2024)
This research explores thematic analysis based on lexical and grammatical cohesion in a journalistic context, especially on news narratives from Al Jazeera newspaper, Mu'jam Mustalahat al-I'lamiyah, and the Dictionary of Press &; Media. The objective of this study is to understand the relationship between form and meaning in the domain of journalism. A descriptive qualitative approach is used to reveal the details of these aspects. The data collection method is focused on literature research to obtain data. In data analysis, lexical and grammatical codes are identified based on content, theme, meaning, and concept description. Lexical cohesion in each news narrative is explained through Word Frequency Analysis to assess the recurrence of words, while the use of linkage markers is assessed to evaluate grammatical fluency. The results revealed the interrelationship between form and meaning, with the identification of 58 forms of Arabic basic word concepts in the form of fi'il madhi and 14 nominal phrase forms, the jumlah-ismiyah. This finding can be applied to enrich the news narrative in the Indonesian journalistic context in the form of 230 journalistic terms and 30 themes related to Middle Eastern journalism.